Decreased Expression of the Human Urea Transporter SLC14A1 in Bone is Induced by Cytokines and Stimulates Adipogenesis of Mesenchymal Progenitor Cells - Komrakova, Marina; Blaschke, Martina; Ponce, Maria Laura; Klüver, Anne; Köpp, Regine; Hüfner, Michael; Schieker, Matthias; Miosge, Nicolai; Siggelkow, Heide (Experimental and Clinical Endocrinology & Diabetes, 2020)
The human urea transporter SLC14A1 (HUT11/UT-B) has been suggested as a marker for the adipogenic differentiation of bone cells with a relevance for bone diseases. We investigated the function of SLC14A1 in different cells models from bone environment. SLC14A1 expression and cytokine production was investigated in bone cells obtained from patients with osteoporosis. Gene and protein expression of SLC14A1 was studied during adipogenic or osteogenic differentiation of human mesenchymal progenitor cells (hMSCs) and of the single-cell–derived hMSC line (SCP-1), as well as in osteoclasts and chondrocytes. Localization was determined by histochemical methods and functionality by urea transport experiments. Expression of SLC14A1 mRNA was lower in cells from patients with osteoporosis that produced high levels of cytokines. Accordingly, when adding a combination of cytokines to SCP-1 SLC14A1 mRNA expression decreased. SLC14A1 mRNA expression decreased after both osteogenic and more pronounced adipogenic stimulation of hMSCs and SCP-1 cells. The highest SLC14A1 expression was determined in undifferentiated cells, lowest in chondrocytes and osteoclasts. Downregulation of SLC14A1 by siRNA resulted in an increased expression of interleukin-6 and interleukin-1 beta as well as adipogenic markers. Urea influx through SLC14A1 increased expression of osteogenic markers, adipogenic markers were suppressed. SLC14A1 protein was localized in the cell membrane and the cytoplasm. Summarizing, the SLC14A1 urea transporter affects early differentiation of hMSCs by diminishing osteogenesis or by favoring adipogenesis, depending on its expression level. Therefore, SLC14A1 is not unequivocally an adipogenic marker in bone. Our findings suggest an involvement of SLC14A1 in bone metabolism and inflammatory processes and disease-dependent influences on its expression.